2013
DOI: 10.1002/cncr.28021
|View full text |Cite
|
Sign up to set email alerts
|

Use and need for psychosocial support in cancer patients

Abstract: BACKGROUND: Cancer patients and their minor children have been shown to experience psychological distress. The objectives of the current study were to 1) describe the need for and use of psychosocial support and 2) determine predictors of family-centered support use in patients with minor children. METHODS: A population-based sample of 1809 patients was recruited via 2 cancer registries. The eligibility criteria were age 25 years to 55 years, an initial diagnosis received no longer than 6 years before this sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Therefore, a single effective intervention may be beneficial for that constellation of symptoms (38). And conversely, specific interventions such as increased psychosocial support with childrearing may lead to improved outcomes (39), for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a single effective intervention may be beneficial for that constellation of symptoms (38). And conversely, specific interventions such as increased psychosocial support with childrearing may lead to improved outcomes (39), for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Where understanding is not yet clear, is how well the psychosocial needs of haematology patients align with those of patients with solid tumours. In many cases, healthcare professionals who work with cancer patients will already be aware of the need for support as demonstrated by research in this area, however, a sound evidence base is required in order to highlight the on-going need [17]for psychosocial support services and to illustrate which needs above others require the greatest attention from clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…The quality assessment took into consideration all information within the resource, which could include multiple web pages or complete Comparisons and study design are not applicable as this paper is investigating internet-accessible resources, not research studies. 2 Family functioning includes communication, cohesion, or flexibility. Resources do not need to use these terms but should be clearly relevant to at least one of these aspects of family functioning.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Parents with cancer want information from health professionals about how to talk to their children about cancer, and what they can do to help their children cope . In a population‐based sample in the United States of America, 68% of parents with cancer wanted more information regarding parenting with cancer . A qualitative Australian study with oncology nurses found that nurses wanted written materials and websites to support them in discussions with parents around communicating with their children and exploring children's emotional concerns .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation